2020
DOI: 10.31413/nativa.v8i4.10103
|View full text |Cite
|
Sign up to set email alerts
|

Teores E Acúmulos De Nutrientes Em Mudas De Maracujazeiros Sob Salinidade Hídrica E Uso De Urina De Vaca

Abstract: Este trabalho objetivou avaliar a concentração e os acúmulos de macronutrientes em mudas de maracujazeiros produzidas com aplicação de urina de vaca e águas salinas. O experimento foi conduzido em delineamento experimental inteiramente casualizado, no arranjo fatorial 2×2×2, correspondente a duas espécies de maracujazeiro (amarelo e roxo), dois níveis de condutividade elétrica da água de irrigação (0,5 dS m-1 e 3,5 dS m-1) e aplicação de urina oxidada de vaca a 0,0% e 5,0% e três repetições. A irrigação com ág… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
3
0
2
Order By: Relevance
“…It should also be noted that excess soluble salts in the soil solution cause a nutritional imbalance due to the effect of reducing the osmotic potential, decreasing the absorption of nutrients and water [49]. A similar trend to the data in this study was reported by [3], when they investigated the use of brackish water in the cultivation of beet in soil fertilized with 100% of the phosphate fertilizer without microorganisms.…”
Section: Post-harvest and Yieldsupporting
confidence: 89%
“…It should also be noted that excess soluble salts in the soil solution cause a nutritional imbalance due to the effect of reducing the osmotic potential, decreasing the absorption of nutrients and water [49]. A similar trend to the data in this study was reported by [3], when they investigated the use of brackish water in the cultivation of beet in soil fertilized with 100% of the phosphate fertilizer without microorganisms.…”
Section: Post-harvest and Yieldsupporting
confidence: 89%
“…The effects of sodium on soil structure also reduces its capacity to store water, thus affecting plant growth, water absorption, and nutrition. It is important to consider that competitive interaction of the saline ions Na + and Clwith nutrients can affect the Cl -/NO 3 -, Na + /Ca +2 , and Na + /K + ratios in the root medium (Freire et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Resultados de pesquisas mostram controvérsias quanto aos efeitos da salinidade na absorção do nutriente fósforo. Freire et al (2020) observaram que a salinidade reduz a concentração de P nos tecidos das plantas. Todavia, há pesquisas que mostram aumento (Navarro et al, 2001) ou nenhum efeito da salinidade sobre o acúmulo desse nutriente (RASHAD; HUSSIEN, 2014).…”
Section: Discussionunclassified